Mechanical Treatment of Raw Waste Lumber an Effective Way to Preserve the Ecology and Resources; IOP Conference Series: Materials Science and Engineering; Vol. 142 : Innovative Technologies in Engineering - Fomin A. A. Anatoly; Gusev V. G. Vladimir; Yudin R. V. Roman; Timerbaev N. F. Nail; Retyunsky O. Yu. Oleg Yurievich (2016, 2016)
Title screen